2021
DOI: 10.1007/s00432-021-03764-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced MRI predicts PTEN protein expression which can function as a prognostic measure of progression-free survival in NPC patients

Abstract: Objectives: The objective of our study was to investigate whether a phosphatase and tensin homolog deleted on chromosome 10 (PTEN) expression was associated with dynamic contrast-enhanced MRI (DCE-MRI) parameters and prognosis in nasopharyngeal carcinoma (NPC). Methods: Two hundred and forty-ve (245) patients with NPC who underwent pretreatment biopsy, PTEN immunohistochemistry of biopsy, and radical intensity-modulated radiation therapy (IMRT) with or without chemotherapy were included. Tumor segmentations we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Lee S et al evaluated the prognostic value of magnetic resonance imaging (MRI)-based radiomics for newly diagnosed NPC in a systematic review and meta-analysis, which showed that MRI-based radiomics revealed an overall modest prognostic value in predicting PFS (mean C-index, 0.76; 95% CI, 0.69-0.84) (28). Wu G et al confirmed that dynamic contrast-enhanced MRI predicts PTEN protein expression, which can function as a prognostic measure of progression-free survival in NPC patients (38). Zhang Lu et al developed a distant metastasis MRI-based model (DMMM), which showed an AUC of 0•792(95% CI, 0•633-0•952) in validation cohorts (7).…”
Section: Discussionmentioning
confidence: 98%
“…Lee S et al evaluated the prognostic value of magnetic resonance imaging (MRI)-based radiomics for newly diagnosed NPC in a systematic review and meta-analysis, which showed that MRI-based radiomics revealed an overall modest prognostic value in predicting PFS (mean C-index, 0.76; 95% CI, 0.69-0.84) (28). Wu G et al confirmed that dynamic contrast-enhanced MRI predicts PTEN protein expression, which can function as a prognostic measure of progression-free survival in NPC patients (38). Zhang Lu et al developed a distant metastasis MRI-based model (DMMM), which showed an AUC of 0•792(95% CI, 0•633-0•952) in validation cohorts (7).…”
Section: Discussionmentioning
confidence: 98%
“…V e refers to the amount of contrast agent every unit DCE-MRI allows. Previous studies reported that pre-treatment K trans and V e maps showed promise for predicting disease-specific survival and monitoring of treatment response in patients with NPC ( 19 , 25 , 26 ). In the present study, the multivariate Cox proportional hazards model suggested that the Radscore was the only independent prognostic biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…With proper quantitative analysis, the data provides functional information on blood flow, vascular permeability, and angiogenesis, in addition to the morphological tumor characteristics used in clinical practice ( 18 ). Quantitative DCE-MRI parameters can be easily derived for each pixel within the tumor using commercially available software and can be visualized in a separate image for each parameter ( 19 ). This makes DCE-MRI a powerful prognostic tool.…”
Section: Introductionmentioning
confidence: 99%
“…CeRNA networks at least partially promote NPC proliferation by inhibiting PTEN expression. PTEN is a tumor suppressor of NPC and a key negative regulatory gene of PI3K/Akt signaling pathway [ 60 , 61 ].…”
Section: Biological Functions Of Lncrna/circrna-mediated Cerna Networ...mentioning
confidence: 99%
“…Low expression of PTEN predicts poor prognosis and shorter progression-free survival in NPC patients [ 61 ]. Overexpression of circITCH significantly inhibits NPC cell proliferation [ 58 ].…”
Section: Biological Functions Of Lncrna/circrna-mediated Cerna Networ...mentioning
confidence: 99%